The Association Between Quality of Nursing Care in the ICU and Severity of Illness - Narges Mohammadi; Mohammad Abdi; Mohammadreza Dinmohammadi (Iran University of Medical Sciences, 2022)
Background: The quality of nursing care can be affected by various factors. This study aims to determine the correlation between the quality of nursing care and the Severity of Illness (SOI) in patients admitted to the Intensive Care Units (ICUs). Methods: This descriptive-correlational study was performed from November 2018 to January 2019 in Ayatollah Mousavi Hospital, Zanjan City, Iran. The sample included 50 ICU patients who were recruited by convenience sampling. The data were collected using the ICU quality of nursing care scale and the sequential organ failure assessment score within the first seven days of hospitalization. They were analyzed by descriptive and non-parametric statistical tests (the Friedman, Wilcoxon signed-rank, and Spearman's rho) using SPSS v. 22 software. The significance level was set as 0.05. Results: The Mean±SD score of quality of nursing care was 86.62±2.19, and there was a significant difference among the seven days (P<0.001). Also, the Mean±SD score of SOI was 6.4±2.31, and it was constant in the first to third days of hospitalization and decreased by the fourth day of admission. There was a significant indirect correlation between the quality of nursing care and SOI from the fourth day onwards (P<0.05). Conclusion: There was a significant inverse relationship between quality of nursing care and SOI from the fourth to the seventh day of hospitalization. It seems that nursing care delivery in the ICU is mainly routine and does not follow the holistic model of care. Therefore, the severity of the illness and the changing needs of ICU patients require that care models be tailored to these changes.